Multi‐round elimination contention‐based multi‐channel MAC scheme for vehicular ad hoc networks. Issue 3 (1st February 2017) - Mao, Yiwei; Yan, Feng; Shen, Lianfeng
Abstract : In this study, the authors propose a multi‐round elimination contention‐based multi‐channel medium access control (VEC‐MAC) scheme for vehicular ad hoc networks. In our proposed scheme, the control channel (CCH) interval is divided into three phases: roadside unit broadcast phase (BP), safety message BP (SBP) and service channel (SCH) reservation phase (RP). On the basis of this division, both the demand of safety‐relevant applications and non‐safety service applications can be satisfied. In addition, through the multi‐round elimination contention in the SCH RP collision probability of transmissions significantly decreases and more successful reservations can be provided. Furthermore, the proposed multi‐round elimination contention‐based multi‐channel MAC for VANETs (VEC‐MAC) can adaptively adjust the length of the CCH interval (CCHI) and the value of the round number for the improvement of the system throughput. Theoretical analysis and simulation results exhibit the superiority of the proposed VEC‐MAC in saturated throughput compared with the variable CCHI MAC and the wireless access in vehicular environment MAC.